Development of Mathematical Modelling Teaching Materials on Mathematics Perception of Junior High School Students - Mifta Nur Hasanah; Darmawijoyo Darmawijoyo; Cecil Hiltrimartin (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
21st century mathematics learning emphasizes students to think critically, communicate, collaborate, and connect mathematics with the real world. This is in line with mathematical modelling which focuses on learning mathematics using real-world phenomena in the process of solving problems that require understanding and interaction. This study aims to produce mathematics teaching materials based on mathematical modelling in the context of Indonesian forest conservation that has criteria for validity, practicality, and a potential effect on students' mathematical perceptions. The type of research used is design research with development studies. Data collection techniques used questionnaires, interviews, and documentation. Teaching materials were declared valid based on expert review questionnaire assessment and student assessment at the one-to-one evaluation stage. The total questionnaire score was 4.59 with a very valid category. Teaching materials are declared practical based on students' comments at the small group stage and analysis of teaching material completion documents at the field test stage. Furthermore, this study uses the principles of developing mathematical modelling problems according to Gailbraith which can produce mathematical modelling teaching materials that have a potential effect on students' mathematical perceptions, with a questionnaire score of 63% in the very good category.Pembelajaran matematika abad-21 menekankan peserta didik untuk berpikir kritis, berkomunikasi, berkolaborasi serta menghubungkan ilmu matematika dengan dunia nyata. Hal tersebut sejalan dengan pemodelan matematika yang memfokuskan pembelajaran matematika menggunakan fenomena dunia nyata dalam proses penyelesaian masalah yang membutuhkan pemahaman serta interaksi. Penelitian ini bertujuan untuk menghasilkan bahan ajar matematika berbasis pemodelan matematika konteks konservasi hutan Indonesia yang memiliki kriteria kevalidan, kepraktisan serta memiliki efek potensial terhadap persepsi matematika peserta didik. Jenis penelitian yang digunakan adalah penelitian design research dengan tipe development studies. Teknik pengumpulan data menggunakan angket, wawancara dan dokumentasi. Bahan ajar dinyatakan valid berdasarkan penilaian angket expert review dan penilaian peserta didik pada tahap one to one evaluation. Total skor angket sebesar 4,59 dengan kategori sangat valid. Bahan ajar dinyatakan praktis berdasarkan komentar peserta didik pada tahap small group dan analisis dokumen penyelesaian bahan ajar pada tahap field test. Selanjutnya, penelitian ini menggunakan prinsip pengembangan soal pemodelan matematika menurut Gailbraith yang dapat menghasilkan bahan ajar pemodelan matematika yang memiliki efek potensial terhadap persepsi matematika peserta didik, dengan skor angket persepsi sebesar 63% berkategori sangat baik.